Genetic selection of elite plants of oil palm using SELEGEN REML / BLUP software - Oliva, Carlos (2014)
Oil palm cultivation is one of the Peruvian Amazon, which generates more interest among investors, which has allowed to install at least 70 thousand of ha. When Peru has entered oil palm seeds of high genetic value, resistance to disease, pests and high performance, but over time has experienced variability in different ecosystems of the country. This study aimed to computerized genetic selection for selection of elite plants of high performance fresh fruit bunches (FFB) of oil palm. For the computerized genetic analysis were available from SELEGEN Rml/Bloop software program that is designed for the analysis and selection. Benin and Ivory Coast are the ones with the best average, the minimum value is 22.1 kg/plant and the maximum value corresponds to 375.9 kg/plant. The 2301 hybrid has the best average performance, followed by the hybrid 2401, the maximum yield extreme values exceeding 340 kg/plant. The first year, the average yield was 46.62 kg/plant and for the third year of production, the average rose to 142.82 kg/pl. Individual performance repeatability for RFF kg/plant in both groups 2007 and 2008 was 0.10 and the repeatability of the average crop was 0.87 and 0.82 for groups 2007 and 2008, respectively. This led to a selective accuracy of 0.93 for 2007 and 0.90 for the group 2008.